1995
DOI: 10.1523/jneurosci.15-10-06926.1995
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of tail-elicited siphon-withdrawal reflex following unilateral axonal injury is associated with ipsi- and contralateral changes in gene expression in Aplysia californica

Abstract: Behavioral, cellular and molecular changes were examined following axonal injury in the marine mollusc Aplysia californica. Unilateral nerve injury was performed by crushing the pleural-pedal connective and the peripheral pedal nerves innervating one side of the posterior body wall and the tail. The injury procedure severs the axons of the pleural sensory neurons resulting in the blockade of the tail-elicited siphon- withdrawal reflex. Partial reflex recovery is observed within 3 d and reaches 50% of the prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…A few short collaterals can be seen emerging from the tip of the regenerating axon. The regenerating axon has not yet crossed the crush site, consistent with our previous studies in intact animals that showed no recovery of the tail-elicited tail-siphon withdrawal reflex at this time point (10). Fig.…”
Section: Fig 2 Injury Increases the Levels Of Cre-binding Proteinssupporting
confidence: 90%
See 2 more Smart Citations
“…A few short collaterals can be seen emerging from the tip of the regenerating axon. The regenerating axon has not yet crossed the crush site, consistent with our previous studies in intact animals that showed no recovery of the tail-elicited tail-siphon withdrawal reflex at this time point (10). Fig.…”
Section: Fig 2 Injury Increases the Levels Of Cre-binding Proteinssupporting
confidence: 90%
“…Collateral elaboration is thought to be a key event in the navigation of axons to the proper target during axonal regeneration as well as during the development of the CNS (3,4). This process appears to involve alterations in gene expression and protein synthesis (5)(6)(7)(8)(9)(10)(11). However, the genomic programs that mediate collateral formation are yet to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Nerve injury reduces cutaneous innervation in the appropriate distal cutaneous territory ipsilaterally 16 and causes later collateral sprouting from adjacent uninjured nerves into hypoinnervated areas. 17 To investigate its contralesional effects, we initiated Wallerian degeneration without infection by performing unilateral axotomies and evaluating the effects on innervation within skin samples from contralateral as well as ipsilesional paw.…”
mentioning
confidence: 99%
“…On the other hand, behavioral recovery can proceed in the absence of regeneration in relevant neurons, as was documented following branchial nerve crush in Aplysia (Hamilton and Fredman, 1998). Similarly, when partial recovery of the siphon withdrawal reflex was found 3 days after the pleural-pedal connective and pedal nerves were crushed unilaterally, the compensatory growth of contralateral sensory neurons was found to be responsible, because the injured neurons regenerate over a period of 6 weeks (Noel et al, 1995). It would be interesting to know if the projections of sensory neurons into the denervated area disappear after the regenerated projections arrive.…”
Section: Neural Regeneration Studied In Vivomentioning
confidence: 89%